Des normes sociales pour les déplacements de population causés par les grands barrages. France, XXe siècle - Armelle Faure (Revue de Géographie Alpine)
With the passage of time and insights from a number of historical studies it is now possible to take a look back at the way rural populations in France were displaced for the construction of large dams during and after the Second World War. Today, international standards relating to the social implications of dam development projects are imposed on dam builders by both governments and financing institutions. However, in the absence of these international social standards, how did population displacements take place in the past? This paper provides a retrospective look in the light of the current "protection policies" developed by the World Bank and the Asian Development Bank. Retrospective case studies are based on research conducted in the Alps by Virginie Bodon on Tignes and Serre-Ponçon for her doctoral thesis in history (1999) and on the book by D. Varaschin on Tignes. The author uses her own studies on the impact of the large dams of the Upper Dordogne, based on research conducted in departmental and municipal archives and on interviews with those who witnessed the implementation of displacement policies and with their children (1998-2005). The author draws on her experience as an anthropologist for the World Bank to analyse the ways in which these displacements were actually carried out. The forced displacements, euphemistically referred to as "involuntary resettlement" in discourses on development, took on increasing notoriety with the international energy crisis.  The dams gave rise to an international debate on their social and environmental impacts, a debate continued by the World Commission on Dams. Today, when financing has again become available for the construction of new dams throughout the world, it seems opportune to provide some insights into the social implications of large dam development projects based on the experience of France, a country that has been, in many respects, one of the most innovative in the implementation of such projects.